KEGIATAN MARKETING PUBLIC RELATION TOKO POLAROID DALAM MEMBANGUN BRAND AWARENES - Arief, Muhammad Muminto; Gahara, Karlina Elvira (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2013)
The development of photography in Indonesia has grown and developed into one of the currently popular lifestyle. It can be seen from the emergence of new habits, which always bring and use a camera wherever they go. In recent times, the world of photography being back again to repeat the past trend, namely that berjeniskan ancient camera instant camera, Polaroid. Amid the rise of the digital world, bringing back Polaroid instant camera new aura with her , where it can be seen that the instant camera is a camera that can produce your own company image directly, a few seconds after the shooting. Since this is an old brand which then rise again of course, required the emergence of brand awareness of the community on this product, to be sold and accepted in the market. Themethod used is descriptive qualitative method. The results obtained are Tokopolaroid marketing public relations strategy to build brand awareness is by publication, doing media identity, conduct and follow the events, makingnews, speech, conduct public service activies, and cooperate with the sponsor. Where to perform these activities will arise seven brand awareness of audience and also make it easier for the audience more aware of Polaroidproducts and increase the purchasing power of public relations marketing strategies have been effective in its implementation Tokopolaroid